nfluence of Red-Bean (Phaseolus vulgaris L)flour Substitution on Phisical, Chemical, and Organoleftic Characteristics of Cookies for Weaning Food - Rizal Damanik; Sri Anna Marliyati; Sumali M Atmojo; Dian Ekawati (Media Gizi dan Keluarga, 2000)
To minimize the effects of antinutrient contents in red bean (Phaseolus vulgaris L) two methods of drying were tested, i.e. oven and drum drier, to produce bean flour. The flour produced then was used as substitute ingredient to make cookies for baby food. The results of this study showed that drum drier are more effective than oven drier as indicated by chemicals and financial analyses. The 50% substitute of bean flour into cookies is preferred by panelists compared to 0% to 40%. This level of substitution has also the cheapest price in production cost. It is recommended that babies should eat 3-4 cookies per day to fulfill the nutrient requirement.